A feedforward controller for tuning laser cladding melt pool geometry in real time. Issue 1 (March 2017) - Moralejo, S.; Penaranda, X.; Nieto, S.; Barrios, A.; Arrizubieta, I.; Tabernero, I.; Figueras, J.
Abstract In this paper, a feedforward proportional-integral (PI) controller is developed to effectively control and tune the laser cladding melt pool geometry in real time. Width setpoint is included in the computer numerically controlled (CNC) programming, making possible its instantaneous change in relation to the position and time, as opposed to conventional controllers that do not have real-time information about these variables. The new concept of variable setpoint at different positions applied to laser cladding represents a great improvement in its use for changeable geometry applications such as blade fabrication. Several experiments are performed to characterize the behaviour of the system, revealing some key factors from monitoring system and image processing crucial for the controller. Laser power is selected as the input control variable, and the clad width is chosen as the output. The width of the melt pool is obtained based on measurements of CMOS camera images and an in-house image processing software algorithm. Closed-loop parameters are identified from the experimental data and Matlab simulations. The architecture of the controller consists on a conventional PI feedback loop and a feedforward module that shows low overshoot and fast response times. Instantaneous connections between laser, CNC, and PC systems allow for knowing the relationship among the exact position and real and setpoint melt pool values. The performance of the controller is verified in the fabrication of cladded parts with variable widths and in real time.